Integrating Indigenous Knowledge into Physics Education: An Ethnophysics Module Based on Serune Kale’ to Enhance Scientific Literacy - Hafnidar Idiani; Susilawati Susilawati; A. Halim; Mohamad Amir Irwan bin Haji Moksin (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Students' scientific literacy in Indonesia remains low based on the results of PISA 2022, particularly in connecting physics concepts with real-world phenomena and local wisdom. This study was conducted to develop an ethnophysics module based on problem-based learning (PBL) that integrates the traditional Acehnese musical instrument, Serune Kale', into the topic of vibrations and sound waves, as well as to examine its feasibility, practicality, and effectiveness in improving students' scientific literacy. The method used in this study was R&D employing the ADDIE model. The research subjects were eighth-grade junior high school students, with a sample consisting of 30 students in the experimental group using the module and 30 students in the control group conventional instruction. The instruments included expert validation sheets, student and teacher response questionnaires, and a scientific literacy test (pretest-posttest) that had been validated (Cronbach's alpha = 0.896). The practicality test obtained an average student response of 97.61% and teacher response of 96.17%, very positive category. The experimental group experienced an improvement in scientific literacy with an average N-Gain of 71.22% (high category), whereas the control group only achieved 17.74% low category. The PBL-based Serune Kale' ethnophysics module was declared valid, practical, and effective in improving students' scientific literacy on the topic of vibrations and sound waves. This study recommends the integration of local wisdom in the development of physics teaching materials as an effort to contextualize learning and preserve culture